2003
DOI: 10.1590/s1413-70542003000200020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different water regimes on the anatomical characteristics of roots of grasses promising for revegetation of areas surrounding hydroelectric reservoir

Abstract: The objective of this study was to evaluate the effect of different water regimes on some aspects of root anatomy of three grasses: Echinochloa pyramidalis (canarana), Setaria anceps (setária) and Paspalum paniculatum (paspalo). The plants were cultivated in a greenhouse and submitted to three water regimes: daily watering; suspension of watering and suspension of watering followed by submersion of the root system. Segments of the middle part of the roots were taken and submitted to classical techniques in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…Root structures found herein for all four species, including P. distichum, are similar to those reported for P. dilatatum by Fabbri et al (2005), Mollard et al (2008), and Vasellati et al (2001) and P. paniculatum (Da Silva et al, 2003), except that our histochemical studies have demonstrated Casparian walls, suberin lamellae, and lignified secondary cell walls in the mostly biseriate exodermis. The exodermal Casparian material in roots is similar to that found for Typha glauca and T. angustifolia by Seago et al (1999), except that Typha exodermis is multiseriate, and the Y-shaped Casparian material is similar to that found in Glyceria maxima by Soukup et al (2007).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Root structures found herein for all four species, including P. distichum, are similar to those reported for P. dilatatum by Fabbri et al (2005), Mollard et al (2008), and Vasellati et al (2001) and P. paniculatum (Da Silva et al, 2003), except that our histochemical studies have demonstrated Casparian walls, suberin lamellae, and lignified secondary cell walls in the mostly biseriate exodermis. The exodermal Casparian material in roots is similar to that found for Typha glauca and T. angustifolia by Seago et al (1999), except that Typha exodermis is multiseriate, and the Y-shaped Casparian material is similar to that found in Glyceria maxima by Soukup et al (2007).…”
Section: Discussionsupporting
confidence: 85%
“…Hubbard, and Paspalum distichum L.) in particular with regard to roots, rhizomes, and stolons (sensu Bell, 2008). Culms and leaves of such grasses have been studied more in detail (Buitenhaus and Veldkamp, 2001;Da Silva et al, 2003;Deshpande and Sarkar, 1961;Fabbri et al, 2005;Hanna et al, 1976;Metcalfe, 1960;Soper, 1956;Vasellati et al, 2001). Accordingly, we focus herein on anatomical features of roots, rhizomes, and/or stolons of these four plants, as they occur in nonflooded conditions that enable the species to be adaptable to their amphibious life styles.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf tissues exposed to drought shows various responses. Thus, in many species such as, Ctenanthe setosa and Triticum aestivum, the entire lamina and mesophyll thickness were reduced under drought stress [2][3][4][5][6][7][8][9][10][11][12][13][14], while it was unaffected by water stress in salvia spendens and Glycine max [13][14][15][16]. Bussotti et al [17] found that limited soil moisture caused a major thickening of the mesophyll, especially in the leaf cuticle and spongy parenchyma of the beech plant, Fagus sylvatica.…”
Section: Introductionmentioning
confidence: 99%
“…However, protoderm and cortex thickness were affected only in the drought sensitive maize (Peña-Valdivia et al, 2005). Some of the above root anatomical responses seem to be adaptations that enhance plant survival in hostile environments (Da Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%